The Lusitanian Amphorae from the Roman Villa of Vale da Arrancada (Portimão, Algarve, Portugal). - Fabião, Carlos (2018)
The Roman villa of Vale da Arrancada is located in the county of Portimão, lying about 4km from the coast and about 1.5km from the Arade River. In 1984, municipal works uncovered a Roman cistern, several structures and a polychrome mosaic. The cistern was totally filled, containing numerous archaeological remains from the Roman period and Late Antiquity. This paper aims to present a systematic analysis of the Lusitanian amphorae recovered inside Vale da Arrancada’s cistern. The various amphora types identified (Almagro 50, Almagro 51c, Algarve 1 and a local ‘Keay 25’ type), mainly produced in Algarve, allowed these productions to be characterized morphologically and the consumption pattern of the Vale da Arrancada villa in its last occupational phase to be glimpsed.